Peningkatan Kemampuan Kognitif Anak melalui Alat Permainan Edukatif Bahan Daur Ulang - Farlina Hardianti; Fithrii Muzdalifah (AS-SABIQUN, 2023)
Learning in Early Childhood Education institutions is learning that applies a learning system through play. All forms of learning in early childhood are mostly done through a game. This is done because this method is more suitable for children who tend to prefer to play. In addition to fun learning, the use of Educational Game Tools (APE) is also a tool that can help the learning process be more enjoyable, because in essence, early childhood learns from real objects. This study aims to improve children's cognitive abilities through recycled material educational tools. This research is a Classroom Action Research (CAR) conducted in group B of Bina Muda Cendekia Kindergarten with 22 children as research subjects. Classroom Action Research (CAR) was carried out in 2 cycles. Data collection techniques in this study used observation and documentation techniques. The results of the study showed that the recycled material educational game tool could improve the cognitive abilities of the children in group B TK Bina Muda Cendekia. In the pre-action stage, the average percentage of achievement for new children reached 45.45%, in the implementation of Cycle I, the percentage achieved was 64.58 and in Cycle II, it was 89.96%.